Peritoneal dialysis resulting in discontinuance of recurring attacks of acute intermittent porphyria: A case report. Issue 1 (24th September 2021) - Østergaard, Maria Grostøl Ørnhøj; Erlandsen, Erland Jørn; Thomsen, Henrik Holm; Randers, Else
Abstract: Acute intermittent porphyria is one of eight disorders arising from disturbances in heme biosynthesis where the precursors, 5‐aminolevulinate and porphobilinogen, are elevated in plasma and urine. Attacks are characterized by severe abdominal pain, vomiting and/or obstipation, neurological manifestations, and psychological disturbances. The mainstay of treatment is hemin infusion to induce the negative feedback of heme synthesis. Hemodialysis is casuistically suggested as an alternative treatment. We present a case report of a 78‐year‐old male with acute intermittent porphyria and renal failure treated with peritoneal dialysis resulting in complete discontinuance of longstanding painful and disabling porphyria attacks.